2011
DOI: 10.1111/j.1526-4637.2011.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Cation-Chloride Cotransporter Inhibitor Furosemide in a Rat Model of Postoperative Pain

Abstract: Intrathecal administration of the CCC inhibitor furosemide had antinociceptive effects in rats with incisional pain. Furosemide may be a novel treatment for postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Sodium-potassium-chloride cotransporter 1 regulates chloride ions influx, while KCC2 adjusts efflux of chloride ions [13][14][15]. The present study showed that, compared with normal rats, NKCC1 expression was higher in spinal dorsal horn of model rats, while the expression of KCC2 was lower in the spinal dorsal horn, which is similar to data from other studies [16][17]. The expression of NKCC1 in spinal dorsal horn of rats in ROPOS group was significantly decreased on the second day.…”
Section: Toxicokinetics Of Ropossupporting
confidence: 90%
“…Sodium-potassium-chloride cotransporter 1 regulates chloride ions influx, while KCC2 adjusts efflux of chloride ions [13][14][15]. The present study showed that, compared with normal rats, NKCC1 expression was higher in spinal dorsal horn of model rats, while the expression of KCC2 was lower in the spinal dorsal horn, which is similar to data from other studies [16][17]. The expression of NKCC1 in spinal dorsal horn of rats in ROPOS group was significantly decreased on the second day.…”
Section: Toxicokinetics Of Ropossupporting
confidence: 90%
“…Yet loop diuretics may have different effects on pain depending on the baseline state of the subject. For example, one study found that intrathecal furosemide increased the pain threshold in rats that had been subjected to trauma but decreased the pain threshold in intact rats [10]. Thus, in the setting of inflammation and NKCC1 upregulation, there may be an increased NKCC1/KCC2 receptor expression and/or activity ratio that would result in a net effect of analgesia after bumetanide exposure.…”
mentioning
confidence: 99%
“…The diuretic effect of furosemide is accomplished by inhibition of the Na . At high concentrations furosemide inhibits platelet aggregation [12], water �lux via aquaporin-1 water channels [13], adenosine transport in erythrocytes [14], postoperative pain in rats [15] and the new permeability pathways (NPP) induced by the malaria pathogens plasmodia in parasitized erythrocytes [16][17][18]. Moreover, furosemide may counteract apoptosis [5,8].…”
Section: Introductionmentioning
confidence: 99%